Response Surfaces in the Numerical Homogenization of Non-Linear Porous Materials - BELUCH, Witold; HATŁAS, Marcin (Engineering Transactions, 2019)
The paper deals with the numerical homogenization of structures made of non-linear porous material. Material non-linearity causes a significant increase in computational costs for numerical homogenization procedure. An application of the response surface methodology allows a significant reduction of the computational effort providing good approximation precision. Finite element method commercial software is employed to solve the boundary-value problem in both scales. Due to the significant reduction in computing time, the proposed attitude may be applied for different optimization and identification tasks for inhomogeneous, non-linear media, especially with the use of global optimization methods.